PERAN DINAS PARIWISATA KOTA BAUBAU DALAM PENGEMBANGAN WISATA BATU SORI - La Gufran; Nastia Nastia (Jurnal Studi Ilmu Pemerintahan, 2022)
This study aims to determine the role of the Baubau City Tourism Office in the Development of Batu Sori Tourism. This research uses descriptive research with a qualitative approach, which is a research method used to examine the condition of natural objects, so the researcher is the key instrument. The results showed that the role of the Baubau City Tourism Office and the Palabusa Village Government in developing stone tourism was carried out through cooperation and encouraging the community and local government to always coordinate. This is in line with the role of the Tourism Office and the Village Government in providing motivation which aims to support the maximization of Batu Sori tourism. Likewise in Batu Sori Tourism Development, the Tourism Office of Baubau City carries out a maintenance program for the Batu Sori tourist area which involves the community as tourism actors with quality infrastructure and facilities that are in accordance with the needs of tourists, and for foreign tourists welcoming activities.